Larvicide Activity and Anti-Mosquito Activity of Several Plants in Indonesia Against Aedes Aegypti: Review Articles - Asman Sadino; Doni Anshar Nuari; Devisi Eka Ariyo Masturoji; Riza Apriani (Buletin Farmatera, 2023)
Abstract: As one of the world's tropical countries with high air humidity, Indonesia is a breeding ground for mosquitoes such as Aedes aegypti, one of the dengue vectors. The search for alternative treatments using plants continues to date. This article review aims to find out and review scientific information from research that has been carried out related to plant activity as larvicide and anti-mosquito. The method of writing this article review uses literature studies through search engines in the form of Google Scholar, PubMed, and NCBI. 27 journals were obtained that were included in the inclusion criteria, The inclusion criteria used are national and international journals that discuss larvicide and anti-plant mosquito activities against Aedes aegypti mosquitoes, Journals published in the last 10 years (2012-2022), and journals in full-text form. From the results of searches related to plants that have activity as a larvicide and anti-mosquito Aedes aegypti, there are as many as 27 plant species, as many as 16 plant species have activity as a larvicide and 11 plant species have activity as anti-mosquito activity. Some of these plants can be used as natural insecticides that are environmentally friendly and contain secondary metabolites such as alkaloids, flavonoids, tannins, phenols, terpenoids, saponins and steroids that are effective as substances that kill larvae and repel mosquitoes.